The Readiness of Students to Learn Interprofessional Teamwork in Antenatal Care - Dina Zakiyyatul Fuadah; Sunartini Hapsara; Mariyono Sedyowinarso (Jurnal Ners, 2014)
Introduction: Indonesia as a developing country have a higher Maternal Mortality Rate (MMR). The prevention efforts is developing interprofessional collaborative practice (IPCP) in the level of health care. Collaboration attitudes should start from education level through interprofessional education training and simulation for student. The objective of this study was to analyze the effect of interprofessional education training toward the readiness of students to learn interprofessional teamwork in antenatal care.Methods: Quasi-experimental design (pre test and post test without control) with Time-Series Design. Participants used in this study were students of five semester in STIKes Karya Husada Kediri year of 2011/2012 and the number of samples are 60 students. Technique sampling using simple random. The data collected by used questionnaires Readiness Interprofessional Learning Scale (RIPLS) and checklist observations using Teamwork Score (TWS). Anova, Friedman test, and Kruskal Wallis was used to statistically analyzed the data.Results: Readiness to learn interprofessional teamwork indicates the value of p = 0.001 thats means there are significant differences between the readiness before and after training IPE. Delta test showed that p value > 0.05 so there is no difference between the three programs study on readiness to learn interprofessional teamwork in antenatal care.Discussion: Interprofessional education training using simulation methods can affect the readiness of nursing, midwifery and nutritionist students for learning interprofessional teamwork in antenatal care.